Uma nova versão: análise dos Elementos de Ficção Presentes nos Cinejornais de João Gonçalves Carriço - Fausto Coimbra Alves Pereira (2009)
The work proposed here wants to verify the political characters construction on documentaries and newsreels presented by João Gonçalves Carriço during the period of 1930 to 1950. The research intends to identify the fictional character of the director's productions and to show when Carriço Film's camera intends to create a positive or negative idea of the political personality presented. This work is supported on theories of image analisys, cinematographycal language and on the historical contextualization of the studied films.